The Improvement Effect of D-Chiro-Inositol and Ecklonia cava K. in the Rat Model of Polycystic Ovarian Syndrome - Yang, Hyun; Lee, Sang R.; Jo, Seong Lae; Kim, Ae-Hyang; Kim, Eun-Ryoung; Qu, Fan; Hong, Eui-Ju; Lee, Hye Won (Frontiers in Pharmacology, 2022)
Introduction: Polycystic Ovarian Syndrome (PCOS) is known to be an endocrine state that is characterized by oligomenorrhea, hyperandrogenism and highly cystic follicles in the ovaries. The use of food ingredients and traditional medicine in Asian countries is well known, and previous studies have shown that Ecklonia cava K. [Alariaceae] (EC) is able to alleviate PCOS symptoms. D-Chiro-inositol (DCI) administration in pathologies where steroid biosynthesis is a crucial factor, i.e., PCOS, has provided satisfactory results. Methods: Therefore, we studied the synergistic effects of the two previously known active compounds. In rats with letrozole-induced PCOS, we focused on alternative therapies using EC and/or DCI extracts to alleviate ovarian failure. Results: As a nonsteroidal aromatase inhibitor, letrozole inhibits the conversion of testosterone to estrogen and subsequently causes PCOS. We divided 6-week-old female mice into the following six groups and evaluated them: vehicle, PCOS, PCOS+MET (metformin), PCOS+DCI, PCOS+EC, and PCOS+DCI+EC. In our study, PCOS rats treated with EC and DCI had low serum LH and T levels and low serum levels of inflammatory cytokines, such as TNFα and IL-6. These treatments also appeared to regulate the production of factors that affect follicle formation and inflammation in the ovaries. Conclusion: We concluded that EC extract and/or DCI administration influenced aromatase production and reduced LH and T stimulation, and cotreatment with EC and DCI consequently restored ovarian dysfunction or anti-inflammatory responses in rats with PCOS-like symptoms.